Bagaimana Umat Islam Bersikap Kepada Ulama, Perspektif Al-Qur’an dan Sunnah - Binti Mazuki, Atiyyah Alya Fatnin; Binti Junaidi, Nurul Fadilah (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
In general, ulama' are people who are knowledgeable, righteous and heirs of the prophet who play a role in preserving and spreading the teachings of Islam. However, the phenomenon of insulting ulama' is becoming more prevalent and increasing, which can lead to social divisions and undermine belief in religious institutions. This study aims to analyse the forms of insult towards the ulama' as well as the views of religion and the public on such issues. This research uses qualitative methods with the analysis of the content of primary sources such as classic books and ulama fatwas, as well as secondary sources in the form of articles and book references. The results of this study show that insult to ulama' is a form of ignorance that can damage the moral behavior of perpetrators and weaken public trust in religious leaders.